ANALISIS PROGRAM PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI KEGIATAN KULIAH KERJA NYATA TEMATIK (KKNT) DI KABUPATEN WONOGIRI - Diansari, Brillian Nur; Alia Akhmad, Khabib; Setiyani, Rahmawati (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2024)
Community economic empowerment is one of the crucial aspects in efforts to improve the welfare and development of a region. Economic empowerment programs, such as Community Service Program, are an effective means of realizing this goal. This research aims to evaluate the effectiveness and impact of the community economic empowerment program through Community Service Program activities in the Wonogiri area. This research is qualitative field research with a phenomenological approach with data collection techniques in the form of observation, interviews and documentation. The data obtained is then processed and analyzed through data reduction, data presentation, and verification or drawing conclusions. The results of Community Service Program activities, although still faced with various challenges, are that the Community Service Program can be implemented smoothly. The conclusion in this research is that there needs to be a strong commitment from universities, local governments, community institutions and village communities themselves. With good cooperation and the right strategy, optimizing Community Service Program can realize inclusive and sustainable development in the village.